2007
DOI: 10.5897/ajb2007.000-2427
|View full text |Cite
|
Sign up to set email alerts
|

SSR markers reveal genetic variation between improved cassava cultivars and landraces within a collection of Nigerian cassava germplasm

Abstract: Thirty-one improved cultivars and five Nigerian landraces of cassava were assessed at genomic DNA level with 16 SSR primers for genetic diversity study. The minimum number of SSR primers that could readily be used for identification of the 36 cassava genotypes was also determined. For the genetic diversity study, the similarity coefficients generated between improved cultivars and Nigerian landraces ranged from 0.42 to 0.84, and 12 distinct DNA cluster groups were identified at 0.70 coefficients using Numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…The results of the analysis of genetic diversity parameters of the 130 accessions showed that the 32 SSR markers were polymorphic with 0.40 as the mean value of PIC. This value was higher than that reported by Moyib et al [53] but lower than those reported by other authors [1,19,54,55]. These differences could be explained by the specificity of each cassava germplasm studied and the SSR markers used.…”
Section: Discussioncontrasting
confidence: 59%
“…The results of the analysis of genetic diversity parameters of the 130 accessions showed that the 32 SSR markers were polymorphic with 0.40 as the mean value of PIC. This value was higher than that reported by Moyib et al [53] but lower than those reported by other authors [1,19,54,55]. These differences could be explained by the specificity of each cassava germplasm studied and the SSR markers used.…”
Section: Discussioncontrasting
confidence: 59%
“…The results of the analysis of genetic diversity parameters of the 130 accessions showed that the 32 SSR markers were polymorphic with 0.40 as mean value of PIC. This value was higher than that reported by Moyib et al [54] but lower than those reported by other authors [1,19,55,56]. These differences could be explained by the specificity of each cassava germplasm studied and the SSR markers used.…”
Section: Discussioncontrasting
confidence: 59%